Creatine monohydrate pilot in Alzheimer's: Feasibility, brain creatine, and cognition - Aaron N. Smith; In‐Young Choi; Phil Lee; Debra K. Sullivan; Jeffrey M. Burns; Russell H. Swerdlow; Emma Kelly; Matthew K. Taylor (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract BACKGROUND Preclinical studies suggest that creatine monohydrate (CrM) improves cognition and Alzheimer's disease (AD) biomarkers. However, there is currently no clinical evidence demonstrating the effects of CrM in patients with AD. METHODS In this single‐arm pilot trial, we investigated the feasibility of 20 g/day CrM for 8 weeks in 20 patients with AD. We measured compliance throughout; serum creatine at baseline, 4 weeks, and 8 weeks; and brain total creatine (tCr) and cognition (National Institutes of Health [NIH] Toolbox, Mini‐Mental State Examination [MMSE]) at baseline and 8 weeks. RESULTS Nineteen participants achieved the target of ≥80% compliance with the CrM intervention. Serum Cr was elevated at 4 and 8 weeks (p < .001) and brain tCr increased by 11% (p < .001). Cognition improved on global (p = .02) and fluid (p = .004) composites, List Sorting (p = .001), Oral Reading (p < .001), and Flanker (p = .05) tests. DISCUSSION Our data suggest that CrM supplementation is feasible in AD and provides preliminary evidence for future efficacy and mechanism studies. Trial Registration ClinicalTrials.gov, NCT05383833, registered on May 20, 2022. Highlights Creatine monohydrate supplementation was feasible in patients with Alzheimer's disease. Creatine monohydrate was associated with increased brain total creatine. Creatine monohydrate was associated with improvements in cognition. Efficacy of creatine monohydrate in Alzheimer's disease should be studied further.